Reconfigurable T‐junction DNA Origami. Issue 37 (15th July 2020) - Young, Katherine G.; Najafi, Behnam; Sant, William M.; Contera, Sonia; Louis, Ard A.; Doye, Jonathan P. K.; Turberfield, Andrew J.; Bath, Jonathan
Abstract: DNA self‐assembly allows the construction of nanometre‐scale structures and devices. Structures with thousands of unique components are routinely assembled in good yield. Experimental progress has been rapid, based largely on empirical design rules. Herein, we demonstrate a DNA origami technique designed as a model system with which to explore the mechanism of assembly. The origami fold is controlled through single‐stranded loops embedded in a double‐stranded DNA template and is programmed by a set of double‐stranded linkers that specify pairwise interactions between loop sequences. Assembly is via T‐junctions formed by hybridization of single‐stranded overhangs on the linkers with the loops. The sequence of loops on the template and the set of interaction rules embodied in the linkers can be reconfigured with ease. We show that a set of just two interaction rules can be used to assemble simple T‐junction origami motifs and that assembly can be performed at room temperature. Abstract : Bringing DNA into the fold : A foldable polymer DNA origami assembled usingT‐junction motifs is presented. It is shown that a set of just two interaction rules can be used to assemble simple T‐junction origami motifs and that assembly can be performed at room temperature.